Cerebellum: links between development, developmental disorders and motor learning - Manto, Mario U. (Frontiers Media S.A., 2012)
The study of the links and interactions between development and motor learning has noticeable implications for the understanding and management of neurodevelopmental disorders. This is particularly relevant for the cerebellum which is critical for sensorimotor learning. The olivocerebellar pathway is a key pathway contributing to learning of motor skills. Its developmental maturation and remodeling are being unraveled. Advances in genetics have led to major improvements in our appraisal of the genes involved in cerebellar development, especially studies in mutant mice. Cerebellar neurogenesis is compartmentalized in relationship with neurotransmitter fate. The Engrailed-2 gene is a major actor of the specification of cerebellar cell types and late embryogenic morphogenesis. Math1, expressed by the rhombic lip, is required for the genesis of glutamatergic neurons. Mutants deficient for the transcription factor Ptf1a display a lack of Purkinje cells and gabaergic interneurons. Rora gene contributes to the developmental signaling between granule cells and Purkinje neurons. The expression profile of sonic hedgehog in postnatal stages determines the final size/shape of the cerebellum. Genes affecting the development impact upon the physiological properties of the cerebellar circuits. For instance, receptors are developmentally regulated and their action interferes directly with developmental processes. Another field of research which is expanding relates to very preterm neonates. They are at risk for cerebellar lesions, which may themselves impair the developmental events. Very preterm neonates often show sensori-motor deficits, highlighting another major link between impaired developments and learning deficiencies. Pathways playing a critical role in cerebellar development are likely to become therapeutical targets for several neurodevelopmental disorders.